2014
DOI: 10.1161/strokeaha.114.005418
|View full text |Cite
|
Sign up to set email alerts
|

Can Response-Adaptive Randomization Increase Participation in Acute Stroke Trials?

Abstract: Background and Purpose A response-adaptive randomization (RAR) trial design actively adjusts the ratio of participants assigned to each trial arm, favoring the better performing treatment by using outcome data from participants already in the trial. Compared to a standard clinical trial, a RAR study design has the potential to improve patient participation in acute stroke trials. Methods This cross-sectional randomized survey included adult emergency department patients, age 18 and over, without symptoms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…Clinical trials in the critically ill are particularly challenging [ 23 ]. Interesting, a hypothetical clinical trial scenario demonstrated greater participation when participants were offered a trial with response adaptive randomization [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials in the critically ill are particularly challenging [ 23 ]. Interesting, a hypothetical clinical trial scenario demonstrated greater participation when participants were offered a trial with response adaptive randomization [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Third, consent discussions should at least explain that adaptive allocation involves allocating some patients to treatments that accumulating evidence disfavors, and that at least in the case of studies using surrogate endpoints and small sample sizes, even if one arm performs better than another, there remains substantial uncertainty about its actual clinical utility. Indeed, were this disclosed to patients, one suspects purported recruitment advantages for adaptive allocation studies [23] would diminish.…”
Section: Resultsmentioning
confidence: 99%
“…The two groups without additional comprehension questions were exposed to the same procedure as the 418 patients from the 2012 study. 3 These scenarios were presented to patients in video form on an iPad. Further details of the protocol are available in the supplemental material, including links to the videos.…”
Section: Methodsmentioning
confidence: 99%
“…If patients understand that they will have an increased chance of benefitting from a trial, then in the use of RAR should lead to an increase in patient participation when compared to standard fixed randomization. 3 However, with the increased complexity of RAR, properly conveying the necessary information about the trial to potential research subjects in a clear, concise, and comprehensible manner becomes even more challenging. In 2012, we presented hypothetical stroke scenarios to 418 emergency department patients at the University of Michigan, and asked them if they would be interested in signing up for the clinical trial based on our presentation.…”
Section: Introductionmentioning
confidence: 99%